Sophia Peabody Hawthorne : A Life, Volume 2, 1848-1871 - Valenti, Patricia Dunlavy, 1945- (Book collections on Project MUSE., 2015)
As is often the case with spouses of celebrities, Sophia Peabody Hawthorne was overshadowed by her husband. While Nathaniel Hawthorne is renowned for numerous publications, including The Scarlet Letter, that staple in high school English curricula, Sophia's remarkable life and career did not receive the recognition they deserve. She was, however, a source for many of Nathaniel's stories and responsible for much that he accomplished. Sophia was an artist, one of the first in America to earn income from her painting and decorative arts; she was also a writer and traveler to foreign countries at a time when women typically confined their activities to the home. Patricia Dunlavy Valenti began to tell this story in Sophia Peabody Hawthorne: A Life, Volume 1, 1809-1847 (2004). This biography concludes now in a second volume, which details the less examined and more surprising second half of Sophia's life. Valenti's thorough research culminates in a compelling, revealing account of Sophia's travels to Britain and Europe and her intense personal relationships outside her marriage with men and women, among them notable figures in American history and literature. As an impoverished widow, Sophia dealt resourcefully with the consequences of her husband's financial carelessness; as a mother, her liberal practices resulted in unintended, sometimes unfortunate consequences. Throughout every vicissitude, her relentless optimism prevailed. With the publication of Sophia Peabody Hawthorne: A Life, Volume 2, 1848-1871, Sophia emerges forever from the shadow cast by her husband. Historians and general readers alike will be drawn to this riveting account of an interesting, important woman and what her life reveals about American history and culture at a moment of national conflict, emerging class divisions, and evolving gender roles.